Surface acoustic wave velocity and elastic constants of cubic GaN - Riobóo, Rafael J. Jiménez; Cuscó, Ramon; Prieto, Carlos; Kopittke, Caroline; Novikov, Sergei V.; Artús, Luis (Japan Society of Applied Physics, 2016)
We present high-resolution surface Brillouin scattering measurements on cubic GaN layers grown on GaAs substrate. By using a suitable scattering geometry, scattering by surface acoustic waves is recorded for different azimuthal angles, and the surface acoustic wave velocities are determined. A comparison of experimental results with numerical simulations of the azimuthal dependence of the surface wave velocity shows good agreement and allows a consistent set of elastic constants for c-GaN to be determined.